Clostridium difficile-derived membrane vesicles promote fetal growth restriction via inhibiting trophoblast motility through PPARγ/RXRα/ANGPTL4 axis - Zhiqiang Zha; Chunhong Jia; Ruisi Zhou; Qinlan Yin; Yu Hu; Zhipeng Huang; Linyu Peng; Yichi Zhang; Xiaowei Qiu; Ying Chen; Yawen Zhong; Yu Wang; et al. (npj Biofilms and Microbiomes)
Abstract Fetal growth restriction (FGR) is a common complication of pregnancy, which seriously endangers fetal health and still lacks effective therapeutic targets. Clostridium difficile (C. difficile) is associated with fetal birth weight, and its membrane vesicles (MVs) are pathogenic vectors. However, the role of C. difficile and its MVs in FGR remains unclear. Here we found that supplementation with C. difficile altered the characteristics of gut microbiota and reduced the birth weight in mice. Interestingly, C. difficile MVs entered placenta, inhibited trophoblast motility, and induced fetal weight loss in mice. Mechanistically, C. difficile MVs activated the PPAR pathway via enhancing the transcriptional activity of PPARγ promoter, consequently inhibiting trophoblast motility. Moreover, PPARγ expression was significantly elevated in FGR placenta, and negatively correlated with fetal birth weight. Together, our findings reveal the significance of C. difficile and its MVs in FGR, providing new insights into the mechanisms of FGR development.